ENT 530 Case Study : Awan Biru Kitchen / Muhammad Haikal Nadzri ... [et al.] - Nadzri, Muhammad Haikal; Azman, Puteri Nurulaina; Mohd Rasman, Ainur Balqis; Jamaludin, Norish Jasmin; Ibrahim, Yusra Irhannan; Saiful Nizam, Farra Nurdeanna (2018)
Awan Biru Kitchen Restaurant is a new restaurant that provide services an eat-in, carryout restaurant, specializing in lunch and evening dining. But this restaurant also provides morning services like "English Breakfast" based on specific time daily. This restaurant is a new medium sized restaurant located in a working neighborhood Cyberjaya, Selangor that operated by Puan Faizah and family. Awan Biru Kitchen Restaurant is recognized as one of the "Asian (Melayu)" restaurant in that areas. Many of people that work in a near the Cyberjaya area get their lunch and often unwind after work to get dinner. Awan Biru Kitchen intends to be part and parcel of this scene, offering superb dish along with convenient carry-out. Relaxed dining in open friendly space during pleasant weather with the best-looking decoration inspired by airlines flight attendance color and experience moments. Comfortable furnishings and décor with soothing warm tones. It will be the perfect place to stop in for a bite to eat, for a gather place or for a small business meeting.